AGRICULTURAL EXTENSION COMMUNICATION PATTERNS IN INCREASING KNOWLEDGE OF VEGETABLE FARMERS - marcelyno, ari; Nainggolan, Dewita Sari; Evadianti, Yuli (Journal of Public Relations and Digital Communication (JPRDC), 2024)
A instructor agriculture need pattern effective communication to use make it easier delivery message or information about agriculture to public or group farmer. Research objectives is know pattern communication counseling agriculture For increase knowledge farmer vegetables and tofu obstacles pattern communication counseling agriculture For increase knowledge farmer vegetables. Type of research is qualitative, the subject of research This instructor agriculture Department of Agriculture Food Crops, Horticulture and Plantation, South Lampung Regency and representatives farmer vegetables in South Lampung Regency. Data analysis was carried out with use technique qualitative data analysis. Based on results study is known that pattern communication instructor agriculture field plant vegetables use pattern communication chain, where results counseling carried out by officers Counselor Field (PPL) carries change knowledge public Good in activity everyday in environment work nor in environment society. Officer Counselor Field (PPL) considers counseling walk effective with use pattern two- way communication, because There is reciprocal flow between instructors and the community happen with good.